The effects of calf muscle self-massage on ankle joint range of motion and tendon-muscle morphology. (October 2022) - Yoshimura, Akane; Sekine, Yuta; Furusho, Atsuya; Yamazaki, Kazuya; Hirose, Norikazu
Abstract: Introduction: Self-massage using a foam roller (foam rolling) has been used to improve joint range of motion (ROM). However, the effect of foam rolling on the morphology of a targeted muscle, tendon, and muscle-tendon unit (MTU) has not been fully clarified. This study aimed to investigate extensibility changes in the gastrocnemius muscle (GM), MTU, and the Achilles tendon (AT) in terms of maximum ankle dorsiflexion (max-DF) following a foam rolling intervention. This was an interventional study with no controls. Methods: Study participants comprised 10 male and female students (mean [standard deviation]: 22.7 [2.5] years; height, 164.2 [6.7] cm; weight, 57.9 [7.9] kg). The foam rolling intervention was performed on the right leg plantar flexor muscles for 3 min. The outcomes were max-DF with specified resistance values (ROM-SR) and non-specified resistance values (ROM-NSR) and GM, MTU, and AT extensibility. An ultrasound device was used to determine the rate of change by subtracting the value in a neutral ankle joint position (0°) from the ankle max-DF to identify GM, MTU, and AT extensibility. All outcomes were measured pre- and post-intervention. Results: The range of ankle joint dorsiflexion increased significantly following the foam rolling intervention (Δ: ROM-SR, +4.35 [5.79]; ROM-NSR, +4.18 [4.43]), whereas GM extensibility increased 4.0 mm, although no significant difference was observed pre- and post-intervention. Conclusion: Foam rolling was effective in increasing ankle joint dorsiflexion ROM. Moreover, it was suggested that the GM morphology might be affected by the intervention. Highlights: ROM-SR and ROM-NSR increased significantly following the foam rolling intervention. A ∼4.0-mm improvement was found in the extensibility of the overall tissues. The extensibility in GM also improved by ∼4.0 mm despite no significant difference. Foam rolling intervention was effective in increasing ankle joint dorsiflexion ROM.